Designing Caricature Illustration book of Paribasan Jawa - Galuh Sekartaji S1 (Saraswati)
know themselves better. Teenagers are easily influenced by the changes in society, there for they need moral support to help them to keep the values in the society. Paribasan Jawa is one of the manifestation of cultural heritage in form of expressions with methaphor, comparison, cause and consequences, and it contains advices functioning as social control. The existance of paribasan Jawa should be preserved to be the moral support in shaping good habbits, therefor designing interesting and communicative educational media is needed.This design is a packaging process of paribasan Jawa into a new form, which is satire caricature with a humorous sense. The design of caricature is the visualisation of a real meaning of paribasan Jawa which is described through 'denotatif' meaning by discussing social reality, and 'konotatif' meaning by adding metaphore containing imagination for entertainment. The design is displayed in the form of caricature illustration book with verbal messages in form of description of each paribasan Jawa meaning, in 2 languages, which are Javanese Language and Bahasa Indonesia to make it easily understood.Designing this caricature illustration book of Paribasan Jawa is one of learning innovations, as well as a new media for guiding and transferring the knowledge to understand the values of Javanese culture easily, so that it can be applied into real actions by means of good habbits in the community.Key words : illustration, caricature, paribasan Jawa, culture.